Smoke Alarms and Smoke Screens: The Learning Journey of an Undergraduate - Anne O'Grady (Educational Futures, 2012)
This research project examined the use of photographs as a valid data collection tool within educational action research. It was a small-scale qualitative study focussing on the lifelong learning journey of BA Education Studies students at the University of Derby.